Toward inclusive and sustainable water and sanitation access: an affordability perspective - Fagundes, Thalita Salgado (2025)
Access to water supply and sanitation services is fundamental to sustainable development, public health, and economic equity. Despite global initiatives to universalize WSS access, significant disparities persist, particularly in low- and middle-income countries, driven by financial constraints, governance challenges, and infrastructure deficiencies. This study critically examines affordability in the WSS sector, proposing actionable strategies for stakeholders to integrate affordability analyses into their decision-making processes. The research identifies the shortcomings of conventional affordability metrics and introduces a multidimensional framework for more precise and inclusive assessments. Focusing on Brazil as a case study, the research provides a comprehensive examination of current affordability, and also the potential impact on affordability of the first water auctions, national performance targets, and legislation on social tariffs, in order to demonstrate that all stakeholders have a critical role on guarantee WSS affordable services. Brazil\'s recent privatization efforts illustrates challenges like uneven rural and urban access and the socio-economic impacts of high auction prices on vulnerable households. Key findings reveal that affordability issues disproportionately affect low-income groups, often overlooked in average-income-based analyses. The study also reveals that tariffs alone may be insufficient to simultaneously sustain and make services affordable, especially if the reliance is exclusively on cross-subsidization. This research advocates for a proactive approach, emphasizing that all stakeholders have the opportunity - and responsibility - to incorporate affordability analyses into their decision-making processes. The study emphasizes the importance of collaboration between governments, utilities, and regulators to ensure equitable access while preserving financial viability. By offering practical insights into subsidy design and affordability-centered governance, this study contributes to global WSS policy discussions, fostering greater inclusivity and alignment with human rights standards.